La emigración y el exilio en la vida de Saturnino Tejera García, entre la Fraternidad y el Periodismo - Sueiro Rodríguez, Victoria María (2015)
Saturnino Tejera García (Santa Cruz de Tenerife, 1900-Cienfuegos, 1956) migrated to Cuba around 1916-1917 and settled down in Yaguajay, and later in Cienfuegos. He was writer, typesetter and non-professional journalist. He started in Freemasonry in 1929 in the Lodge “Fernandina de Jagua”; in 1930 in the Oddfellows lodge “Caballeros de la Luz”. He returned to the Canarian Island at the beginning of the 1930´s. The Spanish Civil War surprised him, and the Supreme Court of Freemasonry in Madrid attacked him for defending his principles. Exiled to Cienfuegos in 1945, he dedicated his efforts to Fraternity and Culture. He had a section in a newspaper, Brotherhood, founded Brotherhood Radio Time, and established the Lodge “Federico Capdevila,” where he was selected Prime Vigilant and representative in the Great Lodge of Cuba. Therefore, the objective of this paper is to assess his significant contributions to local Freemasonry and Journalism.